2018
DOI: 10.1021/acs.jmedchem.8b00172
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Morpholino Thiophenes as Novel Mycobacterium tuberculosis Inhibitors, Targeting QcrB

Abstract: With the emergence of multidrug-resistant strains of Mycobacterium tuberculosis there is a pressing need for new oral drugs with novel mechanisms of action. Herein, we describe the identification of a novel morpholino–thiophenes (MOT) series following phenotypic screening of the Eli Lilly corporate library against M. tuberculosis strain H37Rv. The design, synthesis, and structure–activity relationships of a range of analogues around the confirmed actives are described. Optimized leads with potent whole cell ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 41 publications
0
56
0
Order By: Relevance
“…Recent literature has shown that other QcrB inhibitors (namely, Q203 and TB47) have better efficacy within the acute model of TB infection and when used in combination with first line drugs such as rifampicin and pyrazinamide [30]. Due to the respiratory flexibility of Mtb there have been many reports that the efficacy of QcrB inhibitors might be greatly enhanced by tandem inhibition of the cytochrome bd oxidase based upon in vitro data [21,22,[43][44][45]. However, this dual inhibition concept was strengthened by the impressive in vivo efficacy observed when QcrB inhibitors were evaluated against Mycobacterium ulcerans, a disease-causing strain which lacking cyt-bd oxidase [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent literature has shown that other QcrB inhibitors (namely, Q203 and TB47) have better efficacy within the acute model of TB infection and when used in combination with first line drugs such as rifampicin and pyrazinamide [30]. Due to the respiratory flexibility of Mtb there have been many reports that the efficacy of QcrB inhibitors might be greatly enhanced by tandem inhibition of the cytochrome bd oxidase based upon in vitro data [21,22,[43][44][45]. However, this dual inhibition concept was strengthened by the impressive in vivo efficacy observed when QcrB inhibitors were evaluated against Mycobacterium ulcerans, a disease-causing strain which lacking cyt-bd oxidase [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…The morpholino thiophenes represent another point of diversity in structures that can inhibit QcrB. Compound 6 has an MIC of 0.2 μM, overlays well with Q203 by 2D comparison modeling, and has shown efficacy within the acute murine infection model of tuberculosis [22].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Qp site of the Cyt-bcc-aa3 complex is particularly susceptible to chemical inhibition, as evident from the multitude of structurally diverse and distinct compounds detailed above. It has been consistently observed across several of the studies that characteristic consequences of cytochrome bcc inhibition include a general depletion of intracellular bacterial ATP levels, an upregulation of Cyt-bd oxidase, and an increase in OCR and bacterial respiration due to Cyt-bd [12,76,77,[128][129][130]134,135,155,158]. This compensation by the alternate terminal oxidase leads to an incomplete respiratory shutdown in M. tb, resulting in the bacteriostatic nature of cytochrome bcc inhibitors alone.…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexmentioning
confidence: 95%
“…The morpholino-thiophenes were identified from the Lilly corporate library that was screened in an aerobic whole-cell phenotypic setting against M. tb. The series was extensively profiled and optimised, with the lead of this series having an MIC 90 of 0.24 µM against M. tb, a high-selective index and improved microsomal stability [134]. In an acute model of TB infection, the lead compound The most recent class of Cyt-bcc-aa3 inhibitors identified are the quinazoline derivatives, 2-ethylthio-4-methylaminoquinazolines [77].…”
Section: Inhibitors Of the Cyt-bcc-aa3 Complexmentioning
confidence: 99%